Towards the Genomization of Food? Potentials and Risks of Nutrigenomics as a Way of Personalized Care and Prevention - Galesi, Davide (Italian Sociological Review, 2014)
The paper examines the increasingly pervasive genomization of food, understood as the redefinition of food consumption according to the needs for therapy, disease prevention, and enhanced wellness determined by the characteristics of an individual’s genetic heritage. From this perspective, food is not only medicalized (reconceptualized in relation to its connections with health and diseases), not only pharmacologized (monitored in its physiological effects on the organism), but also genomized (consumed on the basis of correlations with the individual genome). The medicine of care and prevention thus finds a further field in which it can overlap with the medicine of human enhancement, even it is one of the most ordinary and fundamental fields of everyday life. Although the genomization process is still ongoing, it appears advisable to focus on its potential and limitations, with a view to targeting control by the public authorities and welfare systems.